(untitled) (REMUNOM, 2026)
This study analyzes teacher training in contexts of diversity, focusing on the professional dispositions and pedagogical practices mobilized by elementary school teachers in response to the demands of social inclusion. It starts from the following research question: how do teachers in this segment perceive their initial and continuing training in a school setting marked by sociocultural heterogeneity and structural challenges? The theoretical framework articulates Pierre Bourdieu’s theory of action, especially the concepts of habitus, field, and capital, with Paulo Freire’s critical-emancipatory contributions on pedagogical practice and reflective training. Methodologically, this is a qualitative study conducted in a municipal public school in the interior of Ceará, using questionnaires and semi-structured interviews, analyzed using content analysis techniques. The results indicate that teachers’ professional dispositions are strained by gaps in initial training, weaknesses in continuing education policies, and limiting institutional conditions. However, it is evident that collaborative practices and reflective processes within the school offer possibilities for reframing pedagogical work. It is concluded that the consolidation of inclusive education requires training policies that are articulated with school realities and the strengthening of teacher professional development as a situated social practice.